KEMAMPUAN IKAN SEPAT SIAM (Trichogaster pectoralis) DALAM MENGENDALIKAN POPULASI KIAPU (Pistia stratiotes) - Efizon, Deni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Trichogaster pectoralis is a root grazer fish and it may be used to control the population of aquatic weeds such as Pistia stratiotes. To understand the ability of the fish in controlling the weed, a laboratory scaled research has been conducted from May-June 2016. There were 5 treatments applied, namely ±25 (Bm25), ±50 (Bm50), ±75 grams fish (Bm75) that were reared in 16 liter tank completed with ±50 grams P. stratiotes. As controls, ±50 grams weed was reared in tank without any fish (Kk50) and ±50 grams fish (Ki50) was reared in tank without weed. Results shown that T. pectoralis was able to control P. stratiotes population. Each treatment speed up the decrement of P. stratiotes population, but the best result was shown by Bm75. In this treatment, the population of P. stratiotes reduced into 2.7 grams by the 28th day.Keywords: Tricogaster pectoralis, Pistia stratiotes, weed control, root grazer